CYBER WELLBEING IN THE PESANTREN ENVIRONMENT: STRATEGIES TO PREVENT CYBERBULLYING AND GADGET ADDICTION AMONG SANTRI - Sutipyo Ru'iya; Fatima Malik; Hassan Ali (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rapid expansion of digital technology has reshaped communication and learning practices in pesantren, creating both opportunities and risks for santri. Increasing access to smartphones and social media exposes students to cyberbullying, excessive screen time, and gadget dependency, which threaten their psychological wellbeing and disrupt the pesantren’s disciplined learning culture. These challenges highlight the urgent need for a culturally appropriate cyber-wellbeing framework tailored to Islamic boarding schools. This study aims to identify effective strategies for preventing cyberbullying and gadget addiction among santri through a holistic approach that integrates digital literacy, moral education, and behavioral regulation. A mixed-methods design was employed, combining surveys of 312 santri from three pesantren, focus group discussions with ustadz/ustadzah, and observational analysis of daily digital practices. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were thematically coded to capture contextual nuances. The findings reveal that cyberbullying incidents primarily occur through group-chat interactions and anonymous messaging channels, often triggered by peer conflicts and lack of digital etiquette. Gadget addiction was strongly associated with unrestricted device use and absence of structured digital routines. Implementation of three core strategies—digital adab training, gadget-use time management, and monitoring systems involving peer mentors—significantly reduced risky online behaviors. The study concludes that cyber-wellbeing efforts in pesantren must be grounded in Islamic values, community discipline, and collaborative monitoring between teachers and peers. These culturally embedded strategies offer a comprehensive model for strengthening digital resilience among santri in the evolving digital era.